The influence of habitat characteristics on the occupancy and dispersal of two headwater fishes in a dendritic network. Issue 1 (11th January 2023) - Hubbell, Joshua P.; Schaefer, Jacob F.; Kreiser, Brian R.
Abstract: The bifurcating configuration of stream networks impacts the connectivity of patches and therefore influences the effects of habitat variables on dispersal and occupancy. In this study, we developed a comparative framework to explore the influence of environmental and anthropogenic variables on the dispersal and occupancy of two headwater darters, the Yazoo darter ( Etheostoma raneyi ) and goldstripe darter ( Etheostoma parvipinne ). We conducted our study in two subbasins that are nested within a larger Gulf Coastal Plain drainage in the southeastern United States. We examined patterns of occupancy using detection data collected within standardized stream reaches within the larger subbasin. Genotype by sequencing identified single nucleotide polymorphisms, which we then used to calculate genetic distance among samples obtained from localities distributed across both subbasins. Goldstripe darter and Yazoo darter occupancy were both best modeled by a single environmental variable (Yazoo darter: well depth; goldstripe darter: drainage area). Similarly, model rankings suggested that well depth explained a substantial amount of the variability in Yazoo darter genetic distance in this subbasin. However, we found no evidence that drainage area strongly affected goldstripe darter genetic distance within the larger subbasin. Our findings also suggested that the best predictors of Yazoo darter and goldstripe darter genetic distance differed between the two subbasins, and that variation in goldstripe darter genetic distance in the smaller subbasin was largely a consequence of anthropogenic variables. The comparative approach we used in this study suggests that the habitat variables regulating the dispersal and occupancy of some headwater fishes may differ, thus the use of site‐occupancy models to predict the dispersal habitat of these fishes may be inappropriate. Therefore, we suggest that understanding the effects of habitat variables regulating dispersal and occupancy may be crucial to understanding the metapopulation dynamics of headwater fishes.